Prediction of August Atlantic basin hurricane activity - Blake, Eric S., author (Colorado State University. Libraries, 2002)
Although useful seasonal hurricane forecasts for the Atlantic basin are now a reality, large gaps remain in our understanding of observed variations in the distribution of activity within the hurricane season. The month of August roughly spans the first third of the climatologically most active part of the season though activity during this time can be highly variable. Otherwise active hurricane seasons can be very quiet during August while relatively inactive seasons can often be busy during this month. This paper reports on initial investigations of the prospects for forecasting this year-to-year variability of August tropical cyclone (TC) activity. The National Centers for Environmental Prediction/National Center for Atmospheric Research global reanalysis data set is used to identify and evaluate large-scale atmospheric precursor signals for predicting subsequent active versus inactive August periods. It is shown that 55-70 percent of the variance of August TC activity can be hindcast using combinations of three to five global predictive factors that are chosen from a 12 predictor pool with each of the predictors showing precursor associations with TC activity. The most prominent predictive signal is the equatorial July 200 mb wind off the west coast of South America. When this wind is anomalously strong from the northeast during July, Atlantic TC activity in August is almost always enhanced. Other July conditions associated with active Augusts include a weak subtropical high in the north Atlantic, an enhanced subtropical high in the northwest Pacific, and low pressure in the Bering Sea region. One of the many applications of the August-only forecast includes incorporating it into the Gray et al. (1997) seasonal statistical forecast (issued on 1 August) to increase forecast skill for the full season prediction. Most importantly, predicted Net Tropical Cyclone (NTC) activity in August has a significant relationship with the incidence of U.S. August TC landfall events. Better understanding of August-only TC variability will allow for a more complete perspective of total seasonal variability and as such, assist in making better seasonal forecasts.
Also issued as author's thesis (M.S.) -- Colorado State University, 2002.
Keywords: Hurricanes -- Atlantic Ocean -- Forecasting; Cyclone forecasting -- Atlantic Ocean